Comparative Analysis of Microfluidics Thrombus Formation in Multiple Genetically Modified Mice: Link to Thrombosis and Hemostasis - Nagy, Magdolna; van Geffen, Johanna P.; Stegner, David; Adams, David J.; Braun, Attila; de Witt, Susanne M.; Elvers, Margitta; Geer, Mitchell J.; Kuijpers, Marijke J. E.; Kunzelmann, Karl; Mori, Jun; Oury, Cécile; et al. (Frontiers in Cardiovascular Medicine, 2019)
Genetically modified mice are indispensable for establishing the roles of platelets in arterial thrombosis and hemostasis. Microfluidics assays using anticoagulated whole blood are commonly used as integrative proxy tests for platelet function in mice. In the present study, we quantified the changes in collagen-dependent thrombus formation for 38 different strains of (genetically) modified mice, all measured with the same microfluidics chamber. The mice included were deficient in platelet receptors, protein kinases or phosphatases, small GTPases or other signaling or scaffold proteins. By standardized re-analysis of high-resolution microscopic images, detailed information was obtained on altered platelet adhesion, aggregation and/or activation. For a subset of 11 mouse strains, these platelet functions were further evaluated in rhodocytin- and laminin-dependent thrombus formation, thus allowing a comparison of glycoprotein VI (GPVI), C-type lectin-like receptor 2 (CLEC2) and integrin 61 pathways. High homogeneity was found between wild-type mice datasets concerning adhesion and aggregation parameters. Quantitative comparison for the 38 modified mouse strains resulted in a matrix visualizing the impact of the respective (genetic) deficiency on thrombus formation with detailed insight into the type and extent of altered thrombus signatures. Network analysis revealed strong clusters of genes involved in GPVI signaling and Ca2+ homeostasis. The majority of mice demonstrating an antithrombotic phenotype in vivo displayed with a larger or smaller reduction in multi-parameter analysis of collagen-dependent thrombus formation in vitro. Remarkably, in only approximately half of the mouse strains that displayed reduced arterial thrombosis in vivo, this was accompanied by impaired hemostasis. This was also reflected by comparing in vitro thrombus formation (by microfluidics) with alterations in in vivo bleeding time. In conclusion, the presently developed multi-parameter analysis of thrombus formation using microfluidics can be used to: (i) determine the severity of platelet abnormalities; (ii) distinguish between altered platelet adhesion, aggregation and activation; and (iii) elucidate both collagen and non-collagen dependent alterations of thrombus formation. This approach may thereby aid in the better understanding and better assessment of genetic variation that affect in vivo arterial thrombosis and hemostasis.